2021
DOI: 10.3390/agronomy11020240
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Agronomics Increase Grain Yield and Grain Yield Stability of Ultra-Early Wheat Seeding Systems

Abstract: Ultra-early seeding of spring wheat (Triticum aestivum L.) on the northern Great Plains can increase grain yield and grain yield stability compared to current spring wheat planting systems. Field trials were conducted in western Canada from 2015 to 2018 to evaluate the impact of optimal agronomic management on grain yield, quality, and stability in ultra-early wheat seeding systems. Four planting times initiated by soil temperature triggers were evaluated. The earliest planting was triggered when soils reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Using an average wheat grain value of $261.00 Mg -1 (September 2015 to December 2021 average southern Alberta price for CWRS wheat, 13.5% protein content), a grower would expect a gross economic benefit of $117.45 ha -1 by shifting to an ultra-early planting date (Alberta Wheat Commission 2021). Greater grain yield at sites south of 51°N latitude resulting from ultra-early seeding can be attributed to increased plant populations, earlier access to spring soil moisture, drought and heat stress avoidance and a longer vegetative growth period similar to the reports of Kirkegaard et al (2015), Hunt et al (2018), andCollier et al (2021).…”
Section: Ultra-early Wheat Growing Systemmentioning
confidence: 55%
See 4 more Smart Citations
“…Using an average wheat grain value of $261.00 Mg -1 (September 2015 to December 2021 average southern Alberta price for CWRS wheat, 13.5% protein content), a grower would expect a gross economic benefit of $117.45 ha -1 by shifting to an ultra-early planting date (Alberta Wheat Commission 2021). Greater grain yield at sites south of 51°N latitude resulting from ultra-early seeding can be attributed to increased plant populations, earlier access to spring soil moisture, drought and heat stress avoidance and a longer vegetative growth period similar to the reports of Kirkegaard et al (2015), Hunt et al (2018), andCollier et al (2021).…”
Section: Ultra-early Wheat Growing Systemmentioning
confidence: 55%
“…The initial planting date was triggered when soil temperatures first reached 2°C and the second planting date was triggered when soils first reached 8°C. In order to more readily identify any effect of soil-applied residual herbicide activity on spring wheat survival, phytotoxicity and grain yield, the wheat line "LQ1299A", as described in Collier et al (2020Collier et al ( , 2021, was planted at a sub-optimal sowing density of 200 viable seeds m -2 . Previous studies completed by Collier et al (2021) indicated optimal seeding rates increased ultra-early wheat growing system stability and thus, if used in this study, could have served to mask potential negative effects of herbicide applications combined with sub-optimal growing conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations